Handbook of practical program evaluation - Wholey, Joseph S.; Hatry, Harry P.; Newcomer, Kathryn E. 1949- (San Francisco Jossey-Bass, 2010)
"The book is designed to enable students of public policy, policymakers and mangers to obtain useful information and conduct successful systematic evaluations, even under tight resource constraints. This text presents a wide variety of approaches to evaluation through brief, authoritative articles by top academics and practitioners. Thoroughly revised and updated this third edition is filled with the most current information, up-to-date examples, and puts increased emphasis on practical applicability. The third edition also features a new and up-dated instructor's manual"--Provided by publisher.
Includes bibliographical references and indexes.
Keywords: Policy sciences; Political planning -- Evaluation